Kinerja Tangki Septik dan Implikasinya terhadap Emisi Metana dan Pemulihan Energi - Hibatullah, Nisrina; Soewondo, Prayatni; Sintawardani, Neni (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
Decentralized septic tank-based sanitation systems remain the primary choice for domestic wastewater management in developing countries, including Indonesia. However, substandard designs and minimal maintenance result in low treatment performance, environmental pollution, and significant greenhouse gas (GHG) emissions. This study used six domestic septic tank units in Bandung City, using a reverse engineering approach and first-order reaction kinetics modeling to estimate influent pollutant loads, organic load removal efficiencies, and methane generation potential. Variation results showed a high Hydraulic Retention Time (HRT) (2–27 days) and an average Chemical Oxygen Demand (COD) concentration of 9,556 mg/L, far exceeding design standards. Units with long HRTs had COD removal efficiencies of up to 91% and methane production potential of up to 490 m³/year, but all gas was released as fugitive emissions due to the lack of a capture and subsequent treatment system. Scenario modeling based on IPCC guidelines shows that the implementation of technical standards (SNI 2398:2017) and Scheduled Fecal Sludge Treatment (LLTT) can reduce methane emissions by up to 90% (from 13.52 Gg/year to 2.09 Gg/year) and recover 50.3 GWh/year of energy through sludge treatment at Fecal Sludge Treatment Plants (IPLT). These findings confirm that minimal intervention with the integration of sludge management and energy recovery is an effective strategy for climate mitigation and household sanitation systems.